Quantitative temporal analysis of protein dynamics in cardiac remodeling. (August 2018) - McClatchy, Daniel B.; Ma, Yuanhui; Liem, David A.; Ng, Dominic C.M.; Ping, Peipei; Yates, John R.
Abstract: Cardiac remodeling (CR) is a complex dynamic process common to many heart diseases. CR is characterized as a temporal progression of global adaptive and maladaptive perturbations. The complex nature of this process clouds a comprehensive understanding of CR, but greater insight into the processes and mechanisms has potential to identify new therapeutic targets. To provide a deeper understanding of this important cardiac process, we applied a new proteomic technique, PALM (Pulse Azidohomoalanine in Mammals), to quantitate the newly-synthesized protein (NSP) changes during the progression of isoproterenol (ISO)-induced CR in the mouse left ventricle. This analysis revealed a complex combination of adaptive and maladaptive alterations at acute and prolonged time points including the identification of proteins not previously associated with CR. We also combined the PALM dataset with our published protein turnover rate dataset to identify putative biochemical mechanisms underlying CR. The novel integration of analyzing NSPs together with their protein turnover rates demonstrated that alterations in specific biological pathways (e.g., inflammation and oxidative stress) are produced by differential regulation of protein synthesis and degradation. Highlights: Quantitatation of newly-synthesized protein (NSP) changes in an isoproterenol (ISO)-induced cardiac remodeling in the mouse left ventricle. The proteomic dataset revealed a complex combination of adaptive and maladaptive alterations at acute and prolonged time points. Integration of the NSP dataset with protein turnover rates in the ISO model demonstrated differential regulation of protein synthesis and degradation.